Timing of Performing Endoscopic Retrograde Cholangiopancreatography and Inpatient Mortality in Acute Cholangitis: A Systematic Review and Meta-Analysis. Issue 3 (18th March 2020) - Du, Lijun; Cen, Mengsha; Zheng, Xia; Luo, Liang; Siddiqui, Ali; Kim, John J.
Abstract : OBJECTIVES: Although early biliary drainage improves outcomes in patients with acute cholangitis, the optimal time to perform endoscopic retrograde cholangiopancreatography (ERCP) is controversial. Our aim was to evaluate the impact of timing of ERCP on mortality in hospitalized patients with acute cholangitis. METHODS: We searched PubMed, EMBASE, and The Cochrane Library (until February 2019) for studies evaluating the impact of timing of ERCP (<24, <48, and <72 hours from hospitalization) on outcomes in patients with acute cholangitis. The primary outcome was in-hospital mortality. RESULTS: Fourteen observational studies, including 84, 063 patients (mean age = 66 ± 18), met the study criteria. The overall pooled in-hospital mortality with acute cholangitis was 1.9% (95% confidence interval [CI] 1.8%–7.6%), which increased to 4.3% (95% CI 1.8%–8.7%) when administrative database studies were excluded. In 9 studies, ERCP performed <24 compared with ≥24 hours decreased in-hospital mortality (odds ratio [OR] = 0.81, 95% CI 0.73–0.90; I 2 = 0%). In 8 studies, ERCP performed <48 compared with ≥48 hours decreased in-hospital mortality (OR = 0.57, 95% CI 0.51–0.63; I 2 = 0%). In 4 studies, ERCP performed <72 compared with ≥72 hours decreased in-hospital mortality (OR = 0.32, 95% CI 0.15–0.68; I 2 = 0%). Furthermore, hospital stay was reduced in patients receiving ERCP <24 compared with ≥24 hours (mean difference [MD] = 3.2 days, 95% CI 2.3–4.1; I 2 = 78%), <48 compared with ≥48 hours (MD = 3.6 days, 95% CI 2.1–5.1; I 2 = 98%), and <72 compared with ≥72 hours (MD = 4.1 days, 95% CI 0.9–7.3; I 2 = 63%). DISCUSSION: In observational studies, earlier ERCP performed in patients with acute cholangitis, even urgently performed <24 hours from presentation, was associated with reduced mortality. A randomized trial evaluating the impact of urgent ERCP on outcomes is needed.